Identifying patterns and drivers of coral diversity in the Central Indo-Pacific marine biodiversity hotspot. Issue 3 (18th April 2017) - Mihaljević, Morana; Korpanty, Chelsea; Renema, Willem; Welsh, Kevin; Pandolfi, John M.
Abstract: Biodiversity hotspots are increasingly recognized as areas of high taxonomic and functional diversity. These hotspots are dynamic and shift geographically over time in response to environmental change. To identify drivers of the origin, evolution, and persistence of diversity hotspots, we investigated the diversity patterns of reef-building corals (Scleractinia) in the Central Indo-Pacific, a marine biodiversity hotspot for the last 25 Myr. We used the scleractinian fossil record (based on literature and a newly acquired fossil collection) to examine the taxonomic and functional diversity of corals from the Eocene to Pliocene. Our data identify potential drivers of coral diversity through time (and space) in the Central Indo-Pacific by constraining the timing of taxonomic turnover events and correlating them with known environmental changes. Increases in taxonomic diversity, high origination rates, and changes in abundance of functional character states indicate that the origin of the Central Indo-Pacific hotspot occurred during the Oligocene, initially through proliferation of pre-existing taxa and then by origination of new taxa. In contrast to taxonomic diversity, overall functional diversity of Central Indo-Pacific reef-building corals remained constant from the Eocene to the Pliocene. Our results identify global sea level as a main driver of diversity increase that, together with local tectonics, regulates availability of suitable habitats. Moreover, marine biodiversity hotspots develop from both the accumulation of taxa from older biodiversity hotspots and origination of new taxa. Our study demonstrates the utility of a combined literature-based and new collection approach for gaining new insights into the timing, drivers, and development of tropical biodiversity hotspots.